(untitled) (Journal of Comilla Medical College Teachers’ Association, 2026)
Background: Post-Traumatic Stress Disorder (PTSD) is a debilitating psychiatric condition that can develop following exposure to traumatic events, leading to persistent re-experiencing, avoidance, hyperarousal, and negative cognitive changes. It significantly impairs quality of life, social functioning, and overall mental health. While pharmacological treatments are often used to manage symptoms, cognitive behavioral therapy (CBT) has emerged as an evidence-based psychotherapeutic approach that targets maladaptive thoughts and behaviors associated with trauma. Objective: This study aimed to evaluate the role of cognitive behavioral therapy in treating post-traumatic stress disorder (PTSD). Methods: This randomized controlled trial was conducted in the Psychiatry OPD and IPD of Comilla Medical College & Hospital from November 2024 to May 2025. Adults (≥18 years) diagnosed with PTSD according to DSM-5 criteria and able to provide consent were included. Data were analyzed using SPSS version 26. Result: In this study of 95 PTSD patients, 12 weeks of CBT led to a significant reduction in PTSD symptom severity (≈50–60% decrease), with a clinical response rate of 68.4% and remission in 60% of participants. Quality of life improved by approximately 22%, and the adoption of CBT skills was substantial. Benefits were maintained at 2-month follow-up, and dropout was low (≈8–11%), while the control group receiving standard pharmacological treatment showed only modest improvements. Conclusion: This study demonstrates that cognitive behavioral therapy is highly effective in reducing PTSD symptom severity, improving quality of life, and sustaining long-term benefits compared to standard pharmacological treatment alone. The low dropout rate and significant improvements in both primary and secondary outcomes underscore CBT’s feasibility and acceptability in clinical settings. J Com Med Col Teachers’ Asso Jan 2026; 30(1): 21-24